OP0053 HLA DRB1 Amino Acid Position 11 is Strongly Associated with Seropositive Rheumatoid Arthritis in Black South Africans. (23rd January 2014) - Govind, N.; Reynolds, R. J.; Hodkinson, B.; Ickinger, C.; Frost, J.; Ramsay, M.; Causey, Z.; Bridges, S. L.; Tikly, M.
Abstract : Background: The "shared epitope" (SE) encoded by HLA-DRB1 alleles are the strongest association with susceptibility for rheumatoid arthritis (RA). We have previously shown that 90% of black South African (BSA) RA patients carry at least one copy of the SE alleles (1 ). Recently, Valine at amino acid position 11 of the HLA-DRB1 chain was shown to confer the strongest risk in this region for RA in Europeans (2 ). Objectives: To determine the role of amino acids at specific positions in the HLA-DRB1 chain in the risk for seropositive RA in BSA. Methods: Consenting BSA RA patients (n=261) fulfilling the 1987 ACR criteria for RA, >18 years at disease onset, and/or RF or ACPA positive and seen at a single centre in South Africa were studied and compared to ethnically and geographically matched controls (n=362). DNA sequencing of exon 2 was performed using Allele SEQR HLA-DRB1 (Abbot). Four digit high resolution HLA typing was assigned using the Assign software (Conexio Genomics). Alleles were converted to binary variables indicating the presence/ absence of a specific amino acid residue at a given position. A series of linear models were fit to assess whether the joint effect of amino acid residues within each position was a significant source of variation for the presence of RA. Results: Of the 29 amino acid positions examined, amino acid position 11 (p=3.4e-26), 13 (p=1.2e-27), and 33 (p=2.1e-28) were the most highly associated with affectation status. Positions 71 and 74 were less significantly associated with p values of 71 (p=2.6e-05) and 74 (p=0.15). After conditioning on position 11, the effects at the other positions were diminished (position 13: p=0.01; position 33: p=0.004), suggesting that in this sample amino acid position 11 was the primary contributor to the association with HLA DRB1. Within position 11 the odds ratios (95% CI) of association were: Valine= 5.1 (3.7, 7.0), p=1.63e-27; Leucine=1.2 (0.7, 2.0), p=0.5; Aspartic acid=1.1 (0.4, 2.9), p=0.8; Glycine=0.98 (0.6, 1.6), p=0.9; Serine=0.4 (0.3, 0.5), p=2.46e-16; with Proline as the referent. Conclusions: Amino acid Valine at position 11 confers the strongest risk for RA in the HLA DRB1 region in black South Africans. Similar to Europeans Valine was the most highly associated amino acid and conversely Serine was protective. References: Meyer, P. W., Hodkinson, B., Ally, M., Musenge, E., Wadee, A. A., Fickl, H., et al. (2011) HLA-DRB1 shared epitope genotyping using the revised classification and its association with circulating autoantibodies, acute phase reactants, cytokines and clinical indices of disease activity in a cohort of South African rheumatoid arthritis patients. Arthritis Res Ther, 13, R160. Raychaudhuri, S., Sandor, C., Stahl, E. A., Freudenberg, J., Lee, H. S., Jia, X., et al. (2012) Five amino acids in three HLA proteins explain most of the association between MHC and seropositive rheumatoid arthritis. Nat Genet, 44, 291-6. Disclosure of Interest: None Declared